Production optimization and characterization of anticancer enzyme L-Asparaginase from Bacillus Sp. using Moringa Oleifera Seeds - Batool, T.; Makky, Essam A.; M., Khan; M. M., Yusoff (2018)
L-Asparaginase (L-asparagine amino hydrolase 3.5.1.1) constitutes one of the most biotechnologically and bio medically important group of therapeutic enzymes accounting for about 40% of the total worldwide enzyme sales [1, 2]. During current research L-asparaginase, was produced from Bacillus sp. Cultural parameters affecting the production of L-asparaginase were optimized [3]. Maximal yields of L-asparaginase were recorded from 5-day-old culture grown in nutrient broth in presence of Moringa Oleifera seeds as substrate with initial pH 7.0 at temperature 37◦C [4, 5]. Ammonium chloride (1%) and galactose (1%) served as good nitrogen and carbon sources for L-asparaginase production, respectively. Na+and K+ slightly enhanced the productivity of L-asparaginase [6]. The in vitro antioxidant and antitumor activity of partially purified L-asparaginase enzyme was also studied [7]. The enzyme showed a good scavenging activity against DPPH with IC50 value of 81.645µg/mL [8].